Dialects Among Young Italian-Australians: A Shift in Attitude and Perception - Benatti, Ruben; Tarantini, Angela Tiziana (Studia Anglica Posnaniensia, 2017)
The aim of this article is to analyse the relationship that second- and third-generation Italian migrants in Australia have with the Italian dialect of their family. We report on the survey we recently carried out among young Italian-Australians, mainly learners of Italian as a second language. First, we analyse the motivation behind learning Italian as a heritage language. We then move on to describe their self-evaluation of their competence in the dialect of their family, and their perception thereof. Surprisingly, our survey reveals that not only are Italian dialects still understood by most second- and third-generation Italians (contrary to what people may think), but Italian dialects are also perceived by young Italian-Australians as an important part of their identity. For them, dialect is the language of the family, particularly in relation to the older members. It fulfills an instrumental function, as it enables communication with some family members who master neither English nor Italian, but above all, it is functional to the construction of their self and their social identity.